A Map of Markups: Why We Observe Mixed Behaviors of Markups. Issue 2 (7th February 2017) - Kim, Seong‐Hoon; Moon, Seongman
Abstract : This paper proposes an explanation for mixed evidence on the behaviors of markups. The key mechanism consists of two complementary channels through which firms handle uninsurable business losses. One channel is based on cost‐compensating motive, by which firms raise prices to reflect higher losses stochastically associated with higher output levels. The other channel is based on loss‐balancing motive, by which firms lower prices to countervail higher losses stochastically associated with higher output levels. The relative responsiveness of the two channels to a shock depends on each firm's fundamental characteristics and leads to a sharp division of markup cyclicality across sectors.